Designing a Model of Case Method Strategy to Enhance Reading Comprehension in EAP Courses for Higher Education - Syarifuddin Achmad; Sartin Miolo; Muzdalifah Mahmud; Helena Badu (TRANSBAHASA, 2024)
Improving education quality for the 21st century necessitates a strong focus on English Reading Comprehension for Academic Purposes (REAP), particularly in higher education. This competency is essential for enabling students to engage with global information and meet the demands of a competitive, interconnected world. Therefore, enhancing reading comprehension in English is vital, especially by employing a strategy that is innovative, creative, and effective. The Case Method Strategy, rooted in Problem-Based Learning (PBL), is identified as one of the most effective approaches to elevate REAP competencies. This strategy fosters creative thinking, inquiry-based learning, and problem-solving skills, allowing students to analyze academic texts critically. Within the REAP course framework, which aligns with Outcome-Based Education (OBE), the objective is for students to develop metacognitive abilities to interpret complex academic texts at an advanced level. To support the Case Method Strategy, complementary techniques, such as Inquiry Method and Discovery Learning, can be integrated into REAP learning. This study aims to present a comprehensive model for implementing the Case Method Strategy to improve REAP outcomes. Ultimately, the findings contribute valuable insights to English Language Teaching (ELT) by offering an effective, alternative teaching technique that enhances applied linguistics and reading comprehension in university-level education.